2004
DOI: 10.1177/0002764204265344
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Theory in Assessing Peer Courts

Abstract: Over the past decade, peer courts have become an increasingly popular way to divert firsttime and status offenders from the juvenile court, with more than 875 programs nationwide in 2002. With their rise in popularity, some studies have examined peer courts'effectiveness for reducing attendee recidivism, although none have employed social theory for these purposes. The goal of this article is to demonstrate why social theory is necessary for evaluating peer courts. The authors use three classical criminologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In another study, Lott et al (2000) found that although teen court participants in Nebraska rated their teen court experience as valuable, "the participants evidenced very little change of attitude or beliefs." Other researchers have also noted empirical and theoretical limitations in the current research on teen courts Dick et al, 2004;Stickle et al, 2008).…”
Section: Restorative Justicementioning
confidence: 97%
“…In another study, Lott et al (2000) found that although teen court participants in Nebraska rated their teen court experience as valuable, "the participants evidenced very little change of attitude or beliefs." Other researchers have also noted empirical and theoretical limitations in the current research on teen courts Dick et al, 2004;Stickle et al, 2008).…”
Section: Restorative Justicementioning
confidence: 97%
“…The continued relevance of diversion as an alternative to formal adjudication variously hinges on: its cost effectiveness (Aos, 2002;Dick et al, 2004;Levin, 2010); association with reduced risk of recidivism (Benda and Tollet, 1999;Goldson, 2000;Holman and Ziedenberg, 2006;Shelden, 1999;Sulivan et al, 2007;Whitehead and Lab, 2001); increased chances of children and young people receiving appropriate interventions beyond juvenile/youth justice systems (Beck et al, 2006); and reduced chances of negative interference with the continued social development and socialization of children and young people including their schooling and family life (Balfanz et al, 2003;Levin, 2010).…”
Section: Diversion and Juvenile/youth Justice Managementmentioning
confidence: 99%
“…Such labeling by justice system staff often resulted in risk for bias, prejudice, unfair decision making, and lengthy involvement in the justice system (Bilchik, 1998;Devine, Coolbaugh, & Jenkins, 1998). Indeed, utilizing labeling theory as a theoretical framework can be useful in exploring the lived experiences of youth of color in secured facilities and in their communities (Dick, Pence, Jones, & Geertsen, 2004).…”
Section: Conceptual Frameworkmentioning
confidence: 99%